Parameters associated with radiographic distal surface caries in the mandibular second molar adjacent to an impacted third molar - Verena Toedtling; Tim Forouzanfar; Henk S. Brand (BMC, 2023)
Abstract Background To determine the risk factors for the development of radiographic distal surface caries (rDSC) in patients who attend routine dental check-ups during an era of National Institute for Health Care Excellence third molar surgery guidelines. Methods Radiographs taken during routine dental examinations involving 1012 patients from Manchester, UK were accessed. Clinical parameters, oral health, patient demographics, and socioeconomic factors were assessed. Risk factors were identified by multivariate logistic regression analysis. Results The detected rate of rDSC was 63.9% and rDSC was distributed homogenously across all five socioeconomic groups (p = 0.425). Risk factors associated with rDSC (p < 0.001) were identified as partially erupted mesio-angularly impacted mandibular third molars, third molars with compromised molar to molar contact points, loss of lamina dura of ≥ 2 mm, male gender, increasing age, and a higher modified Decayed Missing Filled Tooth score. Conclusion rDSC was significantly associated with the angulation of third molars, the compromised contact position of the adjacent third molar, the periodontal status of the distal aspect of the second molar and the cumulative history of oral health in a population governed by specific third molar guidelines. An active approach to third molar surgical management could reduce rDSC and serve this population, irrespective of patients' socioeconomic or deprivation status.